2022
DOI: 10.31083/j.rcm2302065
|View full text |Cite
|
Sign up to set email alerts
|

Preprocedural features of patients under antihypertensive drugs may help identify responders to renal denervation: a hypothesis-generating study

Abstract: Background: Renal denervation (RDN) is effective to lower systolic blood pressure (SBP) in essential hypertension. However, patient selection under medications remains an important unmet clinical need. Methods: This multicenter study aimed at observing whether preprocedural features associated with increased renin-angiotensin-aldosterone activity influence RDN response. This study enrolled the patients who underwent RDN for uncontrolled hypertension. Medical records were reviewd and patients were divided into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The general characteristics and patient demographics of these studies are summarized in Table 1 . Due to the lack of valid data, the remaining 33 studies were used only for qualitative analysis, 12 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 and their basic characteristics are summarized in Table S2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The general characteristics and patient demographics of these studies are summarized in Table 1 . Due to the lack of valid data, the remaining 33 studies were used only for qualitative analysis, 12 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 and their basic characteristics are summarized in Table S2 .…”
Section: Resultsmentioning
confidence: 99%
“…Two studies with a low risk of bias, which were mainly for qualitative analysis due to the lack of valid data, reported that an increase in renin‐angiotensin‐aldosterone system (RAAS) activity is associated with the efficacy of RDN. 41 , 60 One study reported that patients with increased RAAS activity met at least 1 of the following criteria: (1) >10 mm Hg of office SBP reduction after aldosterone inhibition, (2) aldosterone‐renin ratio>30, or (3) slow flow on the renal angiogram 60 ; patients with these characteristics were inclined to benefit from RDN. The other study reported that the use of aldosterone antagonists was also associated with a decrease in BP after RDN.…”
Section: Resultsmentioning
confidence: 99%